Prevalence and associated factors of anemia among female high school students in Depok City - Thesia Ekawati; Sandra Fikawati; Dian Fitri Nurisfanti; Hilmi Friska (AcTion: Aceh Nutrition Journal, 2026)
Anemia among adolescent girls remains a public health issue that can affect their nutritional status, learning abilities, and reproductive health. However, studies that simultaneously analyze nutritional intake, behavioral, and physiological factors associated with anemia among high school girls in Depok City are limited. This study aimed to identify the factors associated with anemia among female high school students in Depok City, Indonesia. Methods: This cross-sectional study included 165 students from 15 public high schools selected by quota sampling between February and April 2024. Data were collected through hemoglobin measurements using the HemoCue Hb 201+, anthropometry, two 24-hour dietary recalls, and structured questionnaires. Data were analyzed using chi-square tests and multiple logistic regressions. Results: The prevalence of anemia was 53.3%. Low protein intake had the strongest independent association with anemia (odds ratio [OR] = 6.18; 95% confidence interval [CI]: 2.74–13.94; P < 0.001). Other associated factors included undernutrition (OR = 5.27; p = 0.015), low energy intake (OR = 4.84; p = 0.001), insufficient iron intake (OR = 4.76; p = 0.002), nonadherence to weekly iron supplementation (OR = 4.50; p = 0.009), irregular menstrual cycles (OR = 3.95; p = 0.004), and low zinc intake (OR = 2.51; p = 0.034). In conclusion, anemia was prevalent and was associated with nutritional, behavioral, and menstrual factors. Integrated interventions should improve dietary quality, supplementation adherence, menstrual health education, and counseling for undernourished female students.